17th workshop on laboratory rodents (rats and mice) care and use 2023 / Associate Professor Dato’ Dr. Vellayan Subramaniam and Dr. Gurmeet Kaur Surindar Singh - Subramaniam, Vellayan; Surindar Singh, Gurmeet Kaur (Faculty of Pharmacy, 2023)
On March 7 and 8, 2023, Laboratory Animal Facility and Management (LAFAM) at the Faculty of Pharmacy, UiTM Puncak Alam conducted a workshop on the care and use of laboratory rodents. The event was organised with blended lectures and hands-on practical conducted by well-known experts in the fields of rodent husbandry, management, behaviour, medicine, surgery, and post-mortem. This workshop was conducted to highlight the importance of the care and use of laboratory rodents in research. It provided training on how to conduct basic procedures on rodents such as proper restraint techniques, substance dose administration via oral gavage, blood collection techniques, anaesthesia, and euthanasia.